Lannea microcarpa: A Review of its Medicinal Uses, Phytochemistry and Pharmacological Properties - Alfred Maroyi (Journal of Pharmacy and Nutrition Sciences, 2018)
Lannea microcarpa is an important food plant and herbal medicine in West Africa. The present study critically reviewed the medicinal uses, phytochemistry and pharmacological properties of L. microcarpa. The